The influence of green brand image, green awareness, green advertising, and ecological knowledge on green purchase intention and green purchase behaviour of beer Bintang and Heineken products in DKI Jakarta - Adelina, Cynthia; Hutabarat, Zoel (Institute of Computer Science (IOCS), 2023)
Green marketing strategies have become increasingly important in addressing the pressing issue of global warming. Companies are adopting green marketing to shape a positive and competitive brand image in offering environmentally conscious products, which ultimately affects consumer purchasing decisions. This study examines the impact of green brand image, green awareness, green advertising, and ecological knowledge on green purchase intention and green purchase behaviour among Beer Bintang/Heineken consumers in DKI Jakarta. The research collected data from 206 respondents who have purchased and seen advertisements for the beer brand. The research findings indicate that green brand image, green advertising, and ecological knowledge significantly and positively influence green purchase intention. Conversely, green awareness has a negative impact on green purchase intention. Additionally, green purchase intention significantly influences green purchase behaviour. The uniqueness of this study lies in its empirical model for predicting green purchasing decisions in the beer industry in Indonesia. It is hoped that this model can also be used by other environmentally friendly FMCG companies and retail industries to develop marketing strategies to enhance customers' green purchasing decisions. This research contributes to global efforts in addressing climate change and environmental issues through consumer choices based on information